1990
DOI: 10.2307/2409505
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Female Body Size in Red-Winged Blackbirds: The Effects of Timing of Breeding, Social Competition, and Reproductive Energetics

Abstract: We examined opposing selective forces on female body size in the sexually dimorphic red-winged blackbird: social competition favoring larger females, and energetic advantages favoring smaller females. Downhower proposed that selection might drive female birds to be smaller than the optimum for survival, if smaller females were able to exceed their energetic requirements for self-maintenance earlier in the season and therefore breed earlier. Since in most birds the earliest breeders fledge the most young, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Finally, the positive relationship between response song rates and reproductive success might occur because female response song rate is related to a third, unmeasured variable that positively influences reproductive success. For example, in other female songbirds, response to a simulated intruder has been positively related to predator defense behavior (Clutton-Brock, 2009;Cain et al, 2011;Tobias et al, 2012;Cain and Rosvall, 2014), body size (Langston et al, 1990;Martin, 1995;Cain and Ketterson, 2012), and maternal care (Rosvall, 2011a;Cain and Ketterson, 2013). Further, a robust response might also be a reflection of overall activity level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the positive relationship between response song rates and reproductive success might occur because female response song rate is related to a third, unmeasured variable that positively influences reproductive success. For example, in other female songbirds, response to a simulated intruder has been positively related to predator defense behavior (Clutton-Brock, 2009;Cain et al, 2011;Tobias et al, 2012;Cain and Rosvall, 2014), body size (Langston et al, 1990;Martin, 1995;Cain and Ketterson, 2012), and maternal care (Rosvall, 2011a;Cain and Ketterson, 2013). Further, a robust response might also be a reflection of overall activity level.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of size variation in female red‐winged blackbirds are unclear. Social competition appears to favour larger females in some circumstances (Langston et al ., 1990) but not in others (Roberts & Searcy, 1988; Muma & Weatherhead, 1991). In the only direct analysis, Weatherhead & Clark (1994) found that adult female size was under stabilizing selection for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Large birds tended to breed before small birds, and assuming that the effect of body size contributed fully to repeatability, then ∼40% of the repeatability of breeding date could be attributed to differences in female size. Why large birds had an advantage is unclear, but may relate to social dominance (Langston et al 1990) or the ability to mobilize resources for egg‐laying (Fogden and Fogden 1979, Houston et al 1983, 1995, Jones 1991). The fact remains, however, that the majority of individual variation in timing of breeding was not repeatable, and could not be accounted for by differences in body size or condition.…”
Section: Discussionmentioning
confidence: 99%